Navigating Shared Decision-Making in Non-Operative Management of Locally Advanced Rectal Cancer - Gaetani, Racquel S.; Abelson, Jonathan S. (Clinics in Colon and Rectal Surgery, 2025)
The management of locally advanced rectal cancer has evolved significantly with the introduction of total neoadjuvant therapy, which increases rates of clinical complete response and enables select patients to pursue non-operative management through a watch-and-wait strategy. While total mesorectal excision remains the standard curative approach, it is associated with considerable morbidity and long-term impacts on bowel, urinary, and sexual function. In contrast, non-operative management offers organ preservation and improved functional outcomes but carries oncologic uncertainty and requires intensive surveillance. This review examines the comparative benefits and limitations of total mesorectal excision and non-operative management, highlighting their impact on quality of life, recurrence risk, and patient-centered care. It also explores emerging strategies to support shared decision-making, including decision aids and predictive modeling, including risk preference assessments. These tools are essential to support informed, individualized decisions and to promote ethically grounded, evidence-based care in the evolving landscape of rectal cancer management.
Keywords: locally advanced rectal cancer; rectal cancer; shared decision-making; non-operative management; watch-and-wait